2010
DOI: 10.1021/ja908488s
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Electrocatalysis for Oxygen Reduction by Cobalt Porphyrins Adsorbed at Liquid/Liquid Interfaces

Abstract: Molecular electrocatalysis for oxygen reduction at a polarized water/1,2-dichloroethane (DCE) interface was studied, involving aqueous protons, ferrocene (Fc) in DCE and amphiphilic cobalt porphyrin catalysts adsorbed at the interface. The catalyst, (2,8,13,17-tetraethyl-3,7,12,18-tetramethyl-5-p-amino-phenylporphyrin) cobalt(II) (CoAP), functions like conventional cobalt porphyrins, activating O(2) via coordination by the formation of a superoxide structure. Furthermore, due to the hydrophilic nature of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
100
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

6
3

Authors

Journals

citations
Cited by 140 publications
(102 citation statements)
references
References 56 publications
2
100
0
Order By: Relevance
“…The IT step can be catalysed by the presence of various aniline derivatives [9,30] and free-base-or metalloporphyrins [44,45], porphines [42] or phthalocyanines [31] in the organic phase and the desired reduction product (H 2 O versus H 2 O 2 ) can be favoured by interfacial assemblies of cobalt porphyrins [12,32,33] or choice of electron donor [10]. Recently, biphasic O 2 reduction has been achieved under neutral and alkaline conditions [17].…”
Section: Biphasic O 2 Reduction By the Ion Transfer -Electron Transfementioning
confidence: 99%
“…The IT step can be catalysed by the presence of various aniline derivatives [9,30] and free-base-or metalloporphyrins [44,45], porphines [42] or phthalocyanines [31] in the organic phase and the desired reduction product (H 2 O versus H 2 O 2 ) can be favoured by interfacial assemblies of cobalt porphyrins [12,32,33] or choice of electron donor [10]. Recently, biphasic O 2 reduction has been achieved under neutral and alkaline conditions [17].…”
Section: Biphasic O 2 Reduction By the Ion Transfer -Electron Transfementioning
confidence: 99%
“…It was also shown that the 4-electron pathways represented a significant contribution to the current response. 39 using ferrocene as a sacrificial electron donor that does not react with molecular oxygen on the time scale of hours. The reduction mechanism common to all these cobalt porphyrin molecules is shown in Fig.…”
Section: Molecular Electrocatalysismentioning
confidence: 99%
“…For example, it has been shown that oxygen and proton could be reduced to hydrogen peroxide and hydrogen by the strong electron donor decamethylferrocene (DMFc) at the water/1,2-dichloroethane (DCE) interface under aerobic and anaerobic conditions, respectively. 2,3 In the case of oxygen reduction, the catalytic effect of in situ generated interfacial Pt nanoparticles 6 and that of different metalated 4,5,8,9 and freebase porphyrins 7,10 have also been demonstrated, showing that both adsorbed Pt particles and porphyrins can act as oxygen binding sites.…”
mentioning
confidence: 98%
“…Electrocatalytic reactions at the interface between two immiscible electrolyte solutions (ITIES), 1 offer new opportunities for energy research such as hydrogen evolution, 2 oxygen reduction 1,[3][4][5][6][7][8] or carbon dioxide reduction. These reactions can be driven by the interfacial potential difference, called Galvani potential difference, which can either be controlled potentiostatically using a four-electrode potentiostat or chemically by a judicious choice of supporting electrolytes in excess.…”
mentioning
confidence: 99%